Computational and Experimental Modelling of Masonry Walling towards Performance-Based Standardisation of Alternative Masonry Units for Low-Income Housing - De Villiers, Wibke Irmtraut (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.